Adalimumab administration after infliximab therapy is a successful treatment strategy for generalized pustular psoriasis. Issue 2 (15th October 2016) - Matsumoto, Ai; Komine, Mayumi; Karakawa, Masaru; Kishimoto, Megumi; Ohtsuki, Mamitaro
Abstract: We report a case of a 70‐year‐old woman with generalized pustular psoriasis (GPP) who responded well to infliximab therapy and adalimumab therapy after secondary failure of infliximab therapy, but did not respond to ustekinumab therapy. We speculate that the pathogenic factor in this case favored anti‐tumor necrosis factor (TNF)‐α therapy to anti‐interleukin‐12/23 therapy. Herein, we also briefly present three additional cases of treatment with adalimumab after secondary failure of infliximab. GPP is often difficult to treat, and no placebo‐controlled trials have been conducted to guide the use of biologics against it because of a paucity of cases. Infliximab and adalimumab are anti‐TNF‐α antibodies that specifically block the interaction of TNF‐α with its receptors. Infliximab has been reported to be effective, with a rapid clearance of symptoms, even in cases of severe GPP. Adalimumab could be a good biologic candidate that can be administrated after secondary failure of infliximab therapy.